EMPDOCLES’ THEOLOGY - Drozdek, Adam (Myrtia, 2003)
According to Empedocles, the universe is an evolving system made out of four elements molded by love and strife. In this universe, love and strife have no moral connotations. They are cosmic forces. Love is a force that aims at uniting elements, strife at separating them. The interplay between love and strife is kept in check by harmony. The particular way harmony manifests itself in the world is a law of proportions. The laws of harmony do not exist by themselves; they find their seat in the divine Mind, the divine Phren , and as such they are an attribute of God. Empedocles’ God evolves over time. He is a mutable God who evolves from the Phren that permeates the entire sphere, to the Phren that recedes to the outermost sphere of the universe to control it from afar. God the holy Phren is most happy when indwelling the sphere. All other stages of world history are, from God’s perspective, a necessary evil. God is not concerned about our world. Empedocles’ God is not the God of love; he uses love to attain his goal. This world is just a stepping stone for achieving the stage of the sphere.